The New CX Marketing Advantages Model as a Predictor of Marketing Performance of MSMEs - Icin Quraysin; Ngadino Surip Diposumarto; Hari Muharam (Universitas Islam Negeri Raden Mas Said Surakarta, 2024)
Rapid digital transformation and increasingly complex consumer behavior demand new approaches in marketing strategies. To address this issue, this study examines the effect of innovation and digital marketing on the marketing performance of MSMEs in Banten Province, Indonesia, and introduces the New CX Marketing Advantages model, which offers an innovative framework to improve marketing performance, particularly for MSMEs. This study employs a quantitative approach to small and medium enterprises operating in KBLI-10 or the food industry in Banten Province. Through multistage sampling using purposive and proportional random sampling methods, 347 MSME actors were identified as respondents in this study. Data were collected using survey methods and analysed using simple and multiple linear regression involving three stages: instrument testing (validity and reliability tests) and hypothesis testing through structural equation modelling (SEM) with data processing techniques utilising the Confirmatory Factor Analysis (CFA) measurement model. The results show that digital marketing and innovation have a positive and significant effect on marketing performance, both partially and simultaneously. Therefore, this study implies that the more MSMEs engage in innovation and enhance digital marketing efforts, the greater is the opportunity to improve their marketing performance.